Rezultati rekonstrukcije stopala s prostim mišično-kožnim režnjem latissimus dorsi - Košir, Roman (Medicinski razgledi, 1996)
The purpose of the study was to evaluate the results of operative reconstruction of the foot with a musculocutaneous latissimus dorsi free flap. At the Department of Plastic Surgery and Burns, University Medical Centre Ljubijana, 45 feet were treated by surgical repair using a musculocutaneous latissimus dorsi free flap between 1980 to 1994. The condition of the reconstructed foot was evaluated in 8 patients. The assessment was based on the results of a questionnaire completed by the patients, as well as on the results of physical examination (flap status, sensibility), and gait analysis (basic kinematic and kinetic parameters, footprint). Because of the small number of patients the efficacy of reconstruction had to be evaluated for each patient separately. As indicated by the patients' subjective assessment and objective findings, which correlated, reconstruction with a musculocutaneous latissimus dorsi free flap proved successful in all the patients studied. This investigation served as a pilot study for other studies to be carried out on larger series of patients.
Keywords: medicina; medicine; kirurško zdravljenje; stopalo